Earth – Atmosphere – Geospace as an Open Nonlinear Dynamical System - Chernogor, L.F.; Rozumenko, V.T. (Радіоастрономічний інститут НАН України, 2008)
The concept of the Earth-atmosphere-ionosphere-magnetosphere (EAIM) system as a complex open dissipative nonlinear dynamical system whose most important property is trigger mechanisms for energy releases has been validated, the basic aspects of the system paradigm being stated. Highly energetic phenomena in the system have been shown to give rise to a complex cluster of processes and to the reconstruction in the subsystem coupling. The active experiments in the EAIM system have established the limitation of the linear description of the subsystem response to large energy inputs, determined the possibility of the onset of large-scale and global-scale perturbation from local and localized energy releases, as well as revealed and identified the types of waves transferring these disturbances. The majority of highly variable processes in the EAIM system have been determined to be accompanied by energetic particle precipitations from the magnetosphere at middle latitudes.